Suverenitet Bosne i Hercegovine / The Sovereignty of Bosnia and Herzegovina - Lavić, Senadin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
Pepers on the topic of the Sovereignty of Bosnia and Herzegovina.